Comfortable Nursing in the Intraoperative MRI Evaluation Combined with Microsurgery in the Treatment of Functional Area Glioma - Tong Shen; Ran Wang; Xin Zhao; Lin Wang; Ying Li; Ting Liu (Concepts in Magnetic Resonance: Part A, Bridging Education and Research)
This study was aimed to investigate the application value of magnetic resonance imaging (MRI) scanning examination in the preoperative treatment of functional glioma and to analyze the application effect of nursing intervention in the operating room in the treatment of fiber surgery. In this study, 80 patients with functional glioma were included as research objects and randomly rolled into the control group (routine nursing) and the experimental group (comfort nursing intervention in the operating room), with 40 cases in each group. All patients underwent craniocerebral MRI plain scan plus enhanced scan before surgery. The levels of the heart rate, systolic blood pressure, diastolic blood pressure, interleukin-6 (IL-6), cortisol, and anxiety before and after the intervention in the two groups were compared when patients entered the operating room (T1), when anesthesia took effect (T2), at the end of surgery (T3), when patients regained consciousness after surgery (T4), and 1 day after surgery (T5). MRI showed that the main glioma sites were located in the basal ganglia region (26.25%), followed by the central region (20.00%) and the Broca region (17.5%). The levels of IL-6 at T2, T3, and T4 in the control group were 186.45 ± 64.55 ng/L, 287.68 ± 34.59 ng/L, and 488.69 ± 81.14 ng/L, respectively, which were inferior to those at T2 (167.44 ± 15.59 ng/L), T3 (186.25 ± 52.64 ng/L), and T4 (356.57 ± 48.22 ng/L) in the test group. The SAS score of the test group after intervention (45.38 ± 2.02) was lower than that of the control group (51.03 ± 3.65) (P<0.05). The levels of cortisol in the test group (T2 (8.89 1.23 ng/L), T3 (9.23 1.25 ng/L), and T4 (11.78 1.27 ng/L) were lower than those in the control group (T2 (11.58 ± 2.48 ng/L), T3 (12.06 ± 2.82 ng/L), and T4 (13.04 ± 11.78)). In short, preoperative MRI scanning was beneficial to detect the location of glioma in functional area. Comfort nursing in the operating room can effectively relieve the anxiety and depression of glioma patients and improve the adverse psychological conditions of the patients.